Effect of Aerobic-Based Exercise on Psychological Well-Being and Quality of Life Among Older People: A Middle East Study - Shams, Amir; Nobari, Hadi; Afonso, José; Abbasi, Hamed; Mainer-Pardos, Elena; Pérez-Gómez, Jorge; Bayati, Mahdi; Bahrami, Alireza; Carneiro, Lara (Frontiers in Public Health, 2021)
The WHO/EMRO-funded research (RPPH grant 18-92) aimed to evaluate the effects of low and moderate-intensity aerobic exercise on psychological well-being and quality of life (QoL) among older people. Forty-five male Iranian adults aged 65 to 80 years were selected according to the eligibility criteria and randomly assigned to a low-intensity group (LIG) (40-50% of maximum heart rate), moderate-intensity group (MIG) (60-70% of maximum heart rate) or control group (CG). The exercise protocols consisted of 12 weeks of aerobic exercise (two sessions per week). Psychological well-being and QoL were assessed through the Ryff’s Psychological Well-being Scale and the World Health Organization QoL Questionnaire. The statistical analysis for psychological well-being indicated that a significant main group (between-group) (F=11.777, p<0.001, ηp2=0.359), time (within-group) (F=58.983, p<0.001, ηp2=0.584) and interaction effect (group × time) (F=20.146, p<0.001, ηp2=0.490) for PWB total score. Bonferroni post-hoc tests revealed that the PWB total score in the MI group was more significant than both LI (p=0.003) and CO (p<0.001). Results for psychological well-being components including self-acceptance, positive relationships with others, autonomy, purposeful life, and environmental mastery revealed no significant differences (p>0.05). while there was a significant difference between the groups for personal growth component. Bonferroni post-hoc tests revealed that the personal growth in the MI group was more significant than both LI (p=0.028) and CO (p<0.001). Result for QoL indicated significant differences for the main group (between-group) (F=13.277, p<0.001, ηp2=0.387), time (within-group) (F=25.533, p<0.001, ηp2=0.378) and interaction effect (group × time) (F=9.992, p<0.001, ηp2=0.332) for quality of life total scale. Bonferroni post-hoc tests revealed that the QoL total scale in the MI group was more significant than both LI (p=0.003) and CO (p<0.001). Results for QoL components including Physical health, Social relationships, Health environment revealed no significant differences (p>0.05), while there was a significant difference between the groups for the Psychological health component. Bonferroni post-hoc tests revealed that the Psychological health in the MI group was more significant than both LI (p=0.009) and CO (p=0.002). Therefore, aerobic exercise improves psychological well-being and QoL in older adults, moderate-intensity exercise seems to produce higher benefits than low-intensity, demonstrating a positive dose-response relationship.